MOTIVATIONAL FACTORS FOR THE PRACTICE OF HANDBALL FOR CHILDREN AND ADOLESCENTS PARTICIPATING SCHOOLS SPORTS TRAINING IN THE CITY CAXIAS DO SUL – RS (Fiep Bulletin - online, 2011)
In any learning process in various environments, it is necessary that the individual has motivation, and this becomes crucial because it is the mainspring of human behavior, determining the search for any purpose by humans. Thus, this research aimed to determine which are the main reasons that affect children and adolescents in the adherence to programs of sport initiation and why they keep practicing the training schools of the sport of handball. The study included 136 children and adolescents of both sexes, aged between 11 and 15 years, participating in sports launcher of the type of handball in the other clusters of sport initiation of Caxias do Sul. Was used in this study the questionnaire Motivation for the Practice of Sports Samukski and Noce, 2000. Among the many reasons involved for the start of handball, the ones that stand out relate to the love for the sport, learning to play the sport, and health. As to the reasons which currently has the children at handball stands out: the encouragement of family, because he likes to compete, I like challenges, learn new moves and technical sport, and to make friends. Analyzing the responses, we can conclude that both the source intrinsic and extrinsic motivation have great influence in sports practice and adherence to it by children and adolescents. Enjoy and appreciate these sources of motivation is crucial for development as a whole this practitioner, not only thinking about this guy as a future athlete, but also as a citizen.
Keywords: handball; sport initiation; motivational factors